Kehamilan Spontan Pada Wanita 26 Tahun Dengan Riwayat Mucinous Cystadenoma Ovarii Papiler Borderline Malignancy Dan Pasca Kemoterapi - Rini Aryani; Almas Nadifa (Journal of Midwifery and Health Science of Sultan Agung, 2023)
Ovarian carcinoma is one of the most common gynecological cancers in women, third ranking after cervical uterine carcinoma and endometrial carcinoma. In this case a G1P0A0 woman aged 26 years pregnant 39 weeks 2 days with a history of dextra salphingooferectomy in 2016 with hitopathological results of mucinous cystadenoma ovarii papillary borderline malignancy and post chemotherapy. Surgery and chemotherapy therapy can impair fertility by affecting the nervous system or reproductive organs. Conservative surgical therapy (conservative surgical staging) and selection of appropriate chemotherapeutic agents can restore fertility in patients with borderline malignancy.